The efficacy of psychological skills training for enhancing performance in sport: a review of reviews - Lange-Smith, S.; Cabot, J.; Coffee, P.; Gunnell, K.; Tod, D. (International Journal of Sport and Exercise Psychology, 2024)
Psychological skills training (PST) is one approach within sport psychology to enhance athletic performance. A significant amount research documents the efficacy of PST for enhancing performance which has led to numerous reviews. Such is the volume of reviews, that a "review of reviews", or overview, is warranted. This overview aimed to examine reviews summarising the evidence that PST enhances performance in sport. Six online databases were searched electronically, and thirteen journals were searched manually, following which accumulated articles were forward- and backward-searched. A total of 30 systematic, meta-analytic, and narrative reviews were included that (a) reviewed studies involving the application of PST to athletes, and (b) summarised the effects of PST interventions on sport performance, or a motor performance-based surrogate of a sporting task. Data regarding review characteristics, PST interventions reviewed, and outcomes were extracted. Included reviews were assessed using the AMSTAR 2 instrument. 90% of the reviews concluded that PST interventions can enhance performance; however, 97% were rated as critically low in quality. Critically low quality reviews should not be relied on to provide an accurate and comprehensive summary of the available studies, thus the conclusion of this overview is that practitioners must be cautious when making claims about the review-level evidence for their PST interventions. It is suggested that prospective reviewers ensure they draw on current and accepted review methodology so that readers have clarity about the efficacy of the reviewed PST interventions in future research.